Probing putative orbital differentiation effects via Eu2+ spin dynamics in Sr1-xEuxFe2As2 - Radaelli, M.; Piva, M. M.; Souza, J. C.; Lesseux, G. G.; Jesus, C. B. R.; Tobia, Dina; Urbano, R. R.; Rosa, P. F. S.; Pagliuso, P. G. (American Physical Society, 2023)
Fil: Radaelli, M.. Universidade Estadual de Campinas; Brasil